Correlation of traditional evaluation VS rubric for evaluation in dental clinic - Forero Escobar , Diana; Herrera Muñoz, Stella María; Restrepo Villamizar, Claudia Elena (Rastros Rostros, 2022)
The evaluation is considered by the Ministry of National Education as one of the most powerful educational tools to promote effective learning. Education shares its way with the evolution of the human being, since societies, from the most primitive, have relied on teaching to transmit knowledge (customs, values and attitudes), from generation to generation. During the different centuries, education and the form of teaching was shaped according to the place where society prospered. The competency model appears as it addresses current and future global challenges, this model analyzes, criticizes, selects, and applies solutions to life’s problems; because it integrates being, knowledge and doing. The methodology is of mixed type quality-quantitative. The use of the evaluation being is intended to have a standardized and easy-to-use evaluation by any evaluator teacher, with which the evaluation parameters are so clear that it is not provided so that students or teachers consider the evaluation to be right. The application of the rubric showed that the traditional evaluative model has bias according to the application; the assessment of the three dimensions to be, learning to be; learning to know and learning to do is the most difficult dimension to evaluate as this is where the teacher must combine the dimension of learning to do with the dimension of understanding to face a certain situation